ChemInform Abstract: A New Approach to 4, 6‐Disubstituted‐3, 4‐dihydropyran‐2‐ones by Domino Michael Addition‐Cyclization Reaction under PTC Conditions. Issue 14 (April 2015) - Gaggero, Nicoletta; Albanese, Domenico C. M.; Nava, Donatella
Abstract: The new domino process allows the preparation of dithioacetals (III).